Hubungan Perilaku Ibu dengan Pemenuhan Gizi Balita Usia 1-5 Tahun di Wilayah Kerja Puskesmas Laonti Kabupaten Konawe Selatan - Harun, Abdul Azis (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2016)
Lack of fulfillment of nutrition in children can cause stunted growth and development, both physical and psychomotor and mental, and can cause brain cell deficiency. Nutritional problems can be caused by the behavior of the mother in meeting the nutritional needs of her toddler. The purpose of this study was to find out the relationship between maternal behavior and the nutritional fulfillment of toddlers aged 1-5 years in the Laonti Health Center Work Area, South Konawe Regency. This type of research is descriptive analytic using a cross sectional study approach with a sample of 66 respondents, using the Chi square test and the phi coefficient test. The results of the chi square analysis found that there was a moderate relationship between the respondent's knowledge and the fulfillment of Toddler Nutrition (X2 count = 18,780; phi = 0.533), there was a moderate relationship between respondents' attitudes and the fulfillment of Toddler Nutrition (X2 count = 16,269; phi = 0.496), there was a relationship moderate between the respondent's actions with the fulfillment of Toddler Nutrition (X2 count = 15,091; phi = 0.478). It is recommended to the Government of South Konawe Regency, especially the health promotion section to continue to carry out health education, especially about balanced nutrition by paying attention to the traditions and culture of the community and to the Puskesmas it is necessary to increase outreach to the community on how to serve food containing balanced nutrition by optimizing available resources. there are like cadres in the integrated service post